Presence of Extra-Criteria Antiphospholipid Antibodies Is an Independent Risk Factor for Ischemic Stroke - Naranjo, Laura; Ostos, Fernando; Gil-Etayo, Francisco Javier; Hernández-Gallego, Jesús; Cabrera-Marante, Óscar; Pleguezuelo, Daniel Enrique; Díaz-Simón, Raquel; Cerro, Mercedes; Lora, David; Martínez-Salio, Antonio; Serrano, Antonio (Frontiers in Cardiovascular Medicine, 2021)
Background. Ischemic stroke is the most common and severe arterial thrombotic event in Antiphospholipid syndrome (APS). APS is an autoimmune disease characterized by the presence of thrombosis and antiphospholipid antibodies (aPL), which provide a pro-coagulant state. The aPL included in the classification criteria are lupus anticoagulant, anti-cardiolipin (aCL) and anti-β2-glycoprotein-I antibodies (aB2GPI) of IgG and IgM isotypes. Extra-criteria aPL, especially IgA aB2GPI and IgG/IgM anti-phosphatidylserine/prothrombin antibodies (aPS/PT), have been strongly associated with thrombosis. However, their role in the general population suffering from stroke is unknown. We aim 1) to evaluate the aPL prevalence in ischemic stroke patients, 2) to determine the role of aPL as a risk factor for stroke, and 3) to create an easy-to-use tool to stratify the risk of ischemic stroke occurrence considering the presence of aPL and other risk factors. Materials and methods. A cohort of 245 consecutive ischemic stroke patients was evaluated in the first 24 hours after the acute event for the presence of classic aPL, extra-criteria aPL (IgA aB2GPI, IgG and IgM aPS/PT) and conventional cardiovascular risk factors. These patients were followed-up for 2-years. A group of 121 healthy volunteers of the same age range and representative of the general population was used as reference population. The study was approved by the Ethics Committee for Clinical Research (Reference numbers CEIC-14/354 and CEIC-18/182) Results. The overall aPL prevalence in stroke patients was 28% and IgA aB2GPI were the most prevalent (20%). In the multivariant analysis, the presence of IgA aB2GPI (OR 2.40, 95% CI: 1.03-5.53), dyslipidemia (OR 1.70, 95% CI: 1.01-2.84), arterial hypertension (OR 1.82, 95% CI: 1.03-3.22), atrial fibrillation (OR 4.31, 95% CI: 1.90-9.78) and active smoking (OR 3.47, 95% CI: 1.72-6.99) were identified as independent risk factors for ischemic stroke. A risk stratification tool for stroke was created based on these factors (AUC: 0.75). Conclusions. IgA aB2GPI are an important independent risk factor for ischemic stroke. Evaluation of aPL (including extra-criteria) in cardiovascular risk factor assessment for stroke can potentially increase the identification of patients at risk of thrombotic event, facilitating a decision on preventive treatments.